2022
DOI: 10.1002/advs.202204038
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D Deficiency in Vascular Smooth Muscle Cells Ameliorates Abdominal Aortic Aneurysm Through Reducing Putrescine Synthesis

Abstract: Abdominal aortic aneurysm (AAA) is a common vascular disease associated with significant phenotypic alterations in vascular smooth muscle cells (VSMCs). Gasdermin D (GSDMD) is a pore‐forming effector of pyroptosis. In this study, the role of VSMC‐specific GSDMD in the phenotypic alteration of VSMCs and AAA formation is determined. Single‐cell transcriptome analyses reveal Gsdmd upregulation in aortic VSMCs in angiotensin (Ang) II‐induced AAA. VSMC‐specific Gsdmd deletion ameliorates Ang II‐induced AAA in apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 75 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…32,33 GSDMD deficiency in VSMCs ameliorates vascular remodeling in abdominal aortic aneurysm. 34 Our study demonstrated that MaR1 could inhabit VSMC differentiation and pyroptosis induction, thereby reversing hypertensive vascular remodeling.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…32,33 GSDMD deficiency in VSMCs ameliorates vascular remodeling in abdominal aortic aneurysm. 34 Our study demonstrated that MaR1 could inhabit VSMC differentiation and pyroptosis induction, thereby reversing hypertensive vascular remodeling.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, hypertensive stress also activates inflammasome and triggers pyroptosis in VSMCs, which contributes to vascular remodeling 32,33 . GSDMD deficiency in VSMCs ameliorates vascular remodeling in abdominal aortic aneurysm 34 . Our study demonstrated that MaR1 could inhabit VSMC differentiation and pyroptosis induction, thereby reversing hypertensive vascular remodeling.…”
Section: Discussionmentioning
confidence: 61%
“… 437 , 438 Gao et al demonstrated that vascular smooth muscle cell (VSMC)-specific GSDMD defects reduced the incidence of AAA in a mouse model. 439 Mechanistically, GSDMD enhances ER stress-CHOP signaling, which subsequently stimulates the expression of ornithine decarboxylase 1 (ODC1), an enzyme that mediates an increase in putrescine levels. High putrescine triggers a pro-inflammatory switch in VSMCs and increases the vulnerability of mice to the development of Ang II-induced AAA.…”
Section: Gasdermins and Diseasesmentioning
confidence: 99%
“…GSDMD specific deficiency in vascular smooth muscle cells alleviates abdominal aortic aneurysm (AAA) by reducing putrescine compound levels in the aorta. 24 Inhibiting the synthesis of putrescine with difluoromethylornithine (DMFO), a compound in a clinical trial for Neuroblastoma, results in the prevention of AAA development. Thus, DMFO could be a potential drug for AAA treatment with few side effects ( Table 1 ).…”
Section: Overview Of Pyroptosis and Gasdermin-dmentioning
confidence: 99%
“…Thus, DMFO could be a potential drug for AAA treatment with few side effects ( Table 1 ). 24 GSDMD is activated in macrophages and vascular smooth muscle cells in human plaques, which exacerbates atherogenesis; thus, inhibition of GSDMD and pyroptosis in atherosclerosis can be a potential therapeutic target. 72 …”
Section: Overview Of Pyroptosis and Gasdermin-dmentioning
confidence: 99%